Role of the polymorphic immunodominant molecule in entry of Theileria parva sporozoites into bovine lymphocytes - Toye, Philip G.; Musoke, A.J.; Naessens, Jan (American Society for Microbiology, 2014)
Theileria parva is a tick-transmitted apicomplexan parasite that infects cattle and African buffalo. In cattle, it causes a fatal lymphoproliferative disease called East Coast fever. The polymorphic immunodominant molecule (PIM) is expressed by two stages of the parasite: the sporozoite, which is inoculated by the tick to infect mammalian lymphocytes, and the schizont, the established intralymphocytic stage. Here, we demonstrate that monoclonal antibodies (MAb) to PIM can reduce the ability of sporozoites to infect bovine lymphocytes in vitro. This reduction appears to be due to blocking of sporozoite attachment by binding of the MAb to several regions of PIM. Interestingly, one MAb, which recognizes an epitope in the central variable region of PIM, did not inhibit sporozoite infectivity. We also demonstrate that PIM antigen, as a recombinant molecule, can also reduce sporozoite infectivity in vitro by blocking both attachment and internalization of sporozoites. Electron microscopic studies showed that PIM is present in microspheres below the sporozoite surface and is transported to the parasite surface soon after contact with bovine lymphocytes. The results suggest that at least two sporozoite molecules, PIM and the previously described p67, are involved in the entry of T. parva into mammalian lymphocytes.